2015
DOI: 10.1371/journal.pone.0132857
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk Screening 2002 as a Predictor of Postoperative Outcomes in Patients Undergoing Abdominal Surgery: A Systematic Review and Meta-Analysis of Prospective Cohort Studies

Abstract: BackgroundThe nutritional risk screening (NRS 2002) has been applied increasingly in patients who underwent abdominal surgery for nutritional risk assessment. However, the usefulness of the NRS 2002 for predicting is controversial. This meta-analysis was to examine whether a preoperative evaluation of nutritional risk by NRS 2002 provided prediction of postoperative outcomes in patients undergoing abdominal surgery.MethodsA systematic literature search for published papers was conducted using the following onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 23 publications
1
58
0
17
Order By: Relevance
“…Gou [19], in turn, evaluated 337 patients who underwent stomach cancer surgery in a single center and found that complications were more frequently observed in the NRS ≥ 3 group (p < 0.05). A metaanalysis of 11 prospective studies performed by Sun et al [5] likewise confirmed the effectiveness of the scale in the risk assessment of surgical complications (p < 0.00001) and postoperative mortality (p < 0.00001) among patients treated with digestive tract surgery; those with a score of < 3 were also shown to require shorter hospitalization times (p = 0.009) (Tab. V).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Gou [19], in turn, evaluated 337 patients who underwent stomach cancer surgery in a single center and found that complications were more frequently observed in the NRS ≥ 3 group (p < 0.05). A metaanalysis of 11 prospective studies performed by Sun et al [5] likewise confirmed the effectiveness of the scale in the risk assessment of surgical complications (p < 0.00001) and postoperative mortality (p < 0.00001) among patients treated with digestive tract surgery; those with a score of < 3 were also shown to require shorter hospitalization times (p = 0.009) (Tab. V).…”
Section: Discussionmentioning
confidence: 64%
“…In their metaanalysis of 128 randomized clinical trials, Kondrup et al [7] validated the patient-and treatment-related risk factors for malnutrition and proposed the NRS scale as a tool for their assessment. Its effectiveness has been confirmed by a number of studies [5,7,[16][17][18][19]. Budzyński et al [17], for instance, analyzed annual admissions to a selected full-profile centre (more than 15,000 patients, 20,000 hospitalizations) and confirmed the utility of the NRS 2002 in the prognosis of both 14-and 30-day readmission (OR, respectively: 2.44, p < 0.0001 and 2.37 p < 0.001) and in-hospital mortality (OR 13.95, p < 0.001).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations